Sebuah Pembelajaran Penting Perang Falkland/Malvinas: Perspektif Sumber Daya Persenjataan Dan Alutsista - Siregar, Supriadi; Novky Asmoro; Mas Ayu Elita Hafizah; Heri Budi Wibowo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This research focuses on the analysis of the Falkland/Malvinas conflict that occurred in 1982 with the aim of understanding the differences in armament and military equipment resources between Argentina and the United Kingdom, as well as its impact on the outcome of the war. In the introduction section, we outline the research problem, which is the comparison of armament and military equipment between both sides, and describe the purpose and objectives of the research. This research uses a qualitative methodology with a literature review approach to gather data from various secondary sources such as books, scholarly journals, and research reports. This allows researchers to gain a comprehensive understanding of the Falkland/Malvinas war. The results of this research describe the superiority held by the United Kingdom in almost all aspects of armament, including the Sea Harrier fighter aircraft, which proved to be a decisive factor in their victory in aerial combat. The impact of these differences was Argentina's defeat and significant damage. The conclusion of this research highlights the importance of thorough military preparedness, advanced technology, and effective diplomacy in preventing armed conflicts. War will only bring great losses to both sides, as seen in the Falkland/Malvinas War. Therefore, diplomacy should be promoted as a solution to resolve international disputes and avoid unnecessary bloodshed